2017
DOI: 10.1002/smll.201603142
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Films of Self‐Assembled Graphene Quantum Dots for n‐Type Doping of Graphene by UV‐Triggered Charge Transfer

Abstract: The demands to examine components serving as one of the active layers in heterostructures of 2D materials have been recently increasing. Nanomaterials synthesized from a solution process and their self‐assembly can provide a promising route to build a new type of mixed dimensional heterostructures, and several methodologies have been reported previously to construct 2D assemblies from colloidal nanostructures in solution. Graphene quantum dots (GQDs), receiving much interest due to the tunable optical band gap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…Up to date, various doping methods influencing the Fermi level of graphene have been reported including electric field, self-assembled monolayer (SAM), , and photoinduced doping. , Among these, the SAM method is particularly useful due to its stability even in the ambient condition. It can be directly applied to the oxide substrate through silanization and introduction of functional groups at the end of silane can effectively influence the Fermi level of graphene.…”
mentioning
confidence: 99%
“…Up to date, various doping methods influencing the Fermi level of graphene have been reported including electric field, self-assembled monolayer (SAM), , and photoinduced doping. , Among these, the SAM method is particularly useful due to its stability even in the ambient condition. It can be directly applied to the oxide substrate through silanization and introduction of functional groups at the end of silane can effectively influence the Fermi level of graphene.…”
mentioning
confidence: 99%
“…At present, several research studies have previously reported the construction of 2D assemblies from colloidal nanostructures in solution. In 2017, Park et al fabricated a closely packed graphene QD film from colloidal solutions using a self-assembled method, and investigated the optical and electrical characteristics of the heteroaccumulation graphene/graphene QD film structures [ 51 ]. In the self-assembled process, destabilized charged particles are trapped at the liquid/liquid or liquid/air interface.…”
Section: Self-assembly Methods Of Quantum Dotsmentioning
confidence: 99%
“…( b ) FET electron mobilities and hole mobilities of graphene/graphene QD film with respect to the increase in photoinduced doping (The triangles in the figure represent the mobility of the electron and the squares in the figure represent the mobility of hole.) [ 51 ]. Copyright 2017, Small .…”
Section: Figurementioning
confidence: 99%
“…Park et al fabricated a closely packed GQDs film (GQDF) from colloidal solutions using a solvent-assisted LB method, and investigated the optical and electrical characteristics of the heterostacked graphene/GQD film (G/GQDF) structures. 224 It was observed that the GQDF played a role not only as a buffer layer that isolates chemical vapor deposited graphene (CVD graphene) from undesired p-doping but also as a photoactive layer that triggers n-doping of the heterostacked CVD graphene film. Wang et al used a LB technique to fabricate ultrathin, high-quality GQD aggregated films with well-modulated optical properties in a wide range of wavelengths.…”
Section: O N L I N E F I R S Tmentioning
confidence: 99%